2002
DOI: 10.3104/reports.134
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in Portuguese children with Down syndrome

Abstract: -Background -Individuals with Down syndrome have an accelerated process of ageing which is thought to be associated with oxidative stress. Aim -Since Zn/Cu superoxide dismutase is increased by about 50% in children with Down syndrome, glutathione and other less known antioxidant mechanisms were studied to determine whether there were changes in reactive oxygen species. Methods -Plasma reduced and oxidised glutathione and red blood cells enzymes including acid phosphatase, methemoglobin reductase and transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These alterations favor an increase in the oxidative stress commonly found in these subjects. In this context, some studies have demonstrated an increase of nearly 50% in the activity of Cu/Zn superoxide dismutase (SOD) in plasma and erythrocytes of DS patients [5,6]. For some researchers, the alterations demonstrated in the activity of SOD in DS patients are probably due to an increase in the expression of the gene for this enzyme in cells of patients with the presence of an additional chromosome 21 [7].…”
Section: Introductionmentioning
confidence: 99%
“…These alterations favor an increase in the oxidative stress commonly found in these subjects. In this context, some studies have demonstrated an increase of nearly 50% in the activity of Cu/Zn superoxide dismutase (SOD) in plasma and erythrocytes of DS patients [5,6]. For some researchers, the alterations demonstrated in the activity of SOD in DS patients are probably due to an increase in the expression of the gene for this enzyme in cells of patients with the presence of an additional chromosome 21 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Results from a mice model suggest an increase in basal generation of ROS in neurons, probably caused by deficiency in mitochondrial ET. Oxidative imbalance in DS individuals may contribute to accelerated aging [59, 60]. Oxidative damage to protein confirms the role of OS in DS [61].…”
Section: Down’s Syndrome (Ds)mentioning
confidence: 96%
“…Excess of chromosomes leads to overexpression of the SOD1 gene, and to elevated H 2 O 2 levels that cannot be completely eliminated by CAT and GPx, so overproduction of ROS occurs (Figure 2) [22][23][24][25]. SOD1 was found to be 50% higher than normal in various cells and tissues of people with DS, so the SOD1/GPx activity ratio was consequently altered [19,22,[26][27][28][29].…”
Section: Ds Issues Targeted By Nutritional Supplementation 41 Oxidati...mentioning
confidence: 99%